Diagnostic Utility of Serum Glycated Albumin for Diabetes Mellitus and Its Correlation With Hyperlipidemia - Park, Sholhui (Ann Lab Med, 2016)
BACKGROUND: Glycated albumin (GA) is a better marker of short-term glycemic control than glycated hemoglobin (A1c). Dyslipidemia is the main cause of cardiovascular complications in diabetes mellitus (DM). Studies on the correlation of GA with lipid indices are sparse. We investigated the diagnostic utility of GA for DM and its relationship with serum lipid profiles compared with that of A1c. METHODS: The GA enzymatic method was used to determine the diagnostic utility of GA for DM by using samples from 163 normal subjects (group 1) and 102 patients newly diagnosed with type 2 DM (T2DM; group 2). To analyze the lipid profiles, 263 patients with T2DM receiving treatment (group 3) were recruited. RESULTS: GA correlated with A1c (r=0.934, P<0.0001). Linear regression analysis indicated that GA levels were about 2.48 folds those of A1c. In the ROC analysis for GA to diagnose DM, the areas under the curve (0.988, 95% confidence interval 0.972-1.004) was excellent. HDL levels were significantly lower in groups 2 and 3. In group 1, positive correlations were observed between A1c and triglyceride (TG), total cholesterol (TC), LDL, TG/HDL, TC/HDL, and LDL/HDL levels. A negative correlation was observed between HDL and A1c levels. In group 3, HDL levels (P=0.0124 and P=0.0141, respectively) were significantly higher and LDL levels tended to be lower, not statistically significant, in the well-controlled group categorized using the A1c and GA cut-off values. CONCLUSIONS: GA is a potential diagnostic tool for DM. Compared with A1c, GA seems less relevant to dyslipidemia.